2005
DOI: 10.1007/s10620-005-2478-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mesalazine in the Treatment of Symptomatic Diverticular Disease

Abstract: We aimed to improve symptoms by means of mesalazine in symptomatic colonic diverticular disease patients. One hundred seventy outpatients (98 M, 72 F; age, 67.1 years; range, 39-84 years) were assigned to four different schedules: rifaximin, 200 mg bid (Group R1: 39 pts), rifaximin, 400 mg bid (Group R2: 43 pts), mesalazine, 400 mg bid (Group M1: 40 pts), and mesalazine, 800 mg bid (Group M2: 48 pts), for 10 days per month. At baseline and after 3 months we recorded 11 clinical variables (upper/lower abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 25 publications
(36 reference statements)
0
66
2
6
Order By: Relevance
“…Although more recent studies have downscaled the estimates of lifetime risk of the development of diverticulitis from 25% 11,12 to 4%, 13 it remains a major burden of disease for our society. Mesalamine and rifaximin have been proposed for prevention of diverticulatis [14][15][16][17] ; however, larger controlled trials on mesalamine had negative results, 18 leaving laparoscopic or open surgery as the remaining option.…”
Section: Discussionmentioning
confidence: 99%
“…Although more recent studies have downscaled the estimates of lifetime risk of the development of diverticulitis from 25% 11,12 to 4%, 13 it remains a major burden of disease for our society. Mesalamine and rifaximin have been proposed for prevention of diverticulatis [14][15][16][17] ; however, larger controlled trials on mesalamine had negative results, 18 leaving laparoscopic or open surgery as the remaining option.…”
Section: Discussionmentioning
confidence: 99%
“…Mesalazine given at 800 mg twice daily for 10 days a month has a similarly effect to rifaximin (400 mg twice daily) [Di Mario et al 2005]. It must however be emphasized that these data came from a single-center, randomized, open trial.…”
Section: Mesalazinementioning
confidence: 94%
“…[22] The RCT found that, at 3 months, either dose of mesalazine reduced physician-rated global symptom score significantly more than rifaximin 200 mg twice daily (170 people with symptomatic colonic diverticular disease; global symptom score range: 0 = no symptoms to 33 = most severe symptoms; mean score reduction from baseline: 4.3 with mesalazine 400 mg twice daily v 3.9 with mesalazine 800 mg twice daily v 0.8 with rifaximin 200 mg twice daily v 3.9 with rifaximin 400 mg twice daily; P less than 0.05 for either dose mesalazine v rifaximin 200 mg twice daily). There was no significant difference between either dose of mesalazine and rifaximin 400 mg twice daily in global symptom score (difference reported as not significant; P value not reported).…”
Section: Colonic Diverticular Disease Digestive System Disorders Benementioning
confidence: 99%
“…The RCT had several methodological flaws: [22] the study was open label; no details were given about the randomisation protocol; a non-validated physician-rated global symptom scale was used as an outcome measure; no power calculation was performed; and there was no placebo arm. It should be noted that mesalazine was given intermittently in this RCT.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation